The Identification of Special Education Teachers’ Performative Competence in Denpasar - Susilawati, L.K.P.A.; Rustika, I M. (Udayana Journal of Social Sciences and Humanities; Vol 3 No 1 (2019): UJoSSH, Feburary 2019DO - 10.24843/UJoSSH.2019.v03.i01.p10, 2019)
Teachers play very important roles in the teaching and learning process of special schools students who have limited ability and development. Learning process which utilizes communication means becomes an important aspect, thus, teachers must be able to communicate well. Therefore, good ability of verbal and non-verbal communication implemented through communication skill is highly needed. This research focuses on performative competence as a part of the communication competence model. This research employed a qualitative approach with constructivism paradigm. The approach enabled the researcher to investigate the social construction of special education teachers’ performative competence in responding to the learning process of special need students at school. The data were collected through an interview by recording and observation. The results reveal that special education teachers show different performative competence and adjust the student’s academic competence.